Peran Perguruan Tinggi Manajemen dalam Penanganan Stunting - Ibnu Khayath Farisanu; Indri Farradina; Achmad Aprianor Firdaus; Muhammad Akbar; Achmad Syahruddin; Hj. Erni Susanti; M. Yunus Syam (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2026)
Stunting is a complex public health problem that requires a multisectoral approach in its management. This community service aims to increase the capacity of village officials and Village Consultative Body (BPD) in handling stunting through the strategic role of management higher education institutions. The method used is a participatory approach involving 18 participants consisting of village officials and BPD members. The activities were carried out through stages of needs analysis, stunting program management training, action plan development assistance, and monitoring evaluation. The results showed a significant increase in participants' understanding of stunting program management (from 45% to 85%), the formation of a stunting management working team at the village level, and the preparation of a comprehensive stunting management action plan. The social change that has been realized is increased cross-sectoral coordination in handling stunting and the formation of a data-based monitoring system at the village level. Management higher education institutions play a strategic role in building the managerial capacity of village officials to manage stunting programs effectively and sustainably.